Book Reviews - Shandir Ramlagan (Taylor & Francis Group, 2009)
Blood-borne HIV: Risks and Prevention By Mariette Correa, David Gisselquist and Deodatta Hari Gore. Hyderabad: Orient Longman Private Ltd. ISBN 13: 978-81-250-3462-9 and ISBN 10: 81-250-3462-5 Reviewed by Shandir Ramlagan.